New Territories: Reimagined Interiorities - Marlor, Lucy (Interiority, 2021)
At a time where boundaries within society, culture, and technology are continually challenged and redefined, even the commonly understood binary oppositions within areas such as gender, age, and digitality (Negroponte, 1995) are becoming less visible, measurable, and socially accepted. In this new realm where even physical reality is encroached upon by the digital, are the tangible and perceived distinctions between interior and architecture also becoming extinct? The emergence of more flexible and transitional space appears to not only blur the boundaries of inside and outside, interior and architecture, but also the previous distinctions of function. Space is no longer solely intimated by visual cues, materiality, or the physicality of walls and interior objects. Instead, we see increased ‘function neutrality’ within buildings, with rising opportunity for user interpretation and take-over. This renewed focus on the user can enrich our built environment as we embrace new equality of the interior and relish its new freedom and voice.